FUNGSI PENGAWASAN DPRD DALAM PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH KABUPATEN MERAUKE - Vincenso Serano (SOCIETAS, 2015)
The present research was aimed to identify how controlling function was implemented in the APBD (Local Budget) and their obstacles encountered and efforts to perform in solving problems of good governance realization.         Method used was gualitative-descriptive method by analyzing and interpreting primary and secondary results of interviews and observation obtained in the research.Based on results and analyses, it was found that controlling function that the DPRD (Local Legislative Assembly) on the APBD in Merauke districk regency had not been optimally performed yet. This was true in planning/arrangement stages of the APBD ( Local Budged Draft ), the mechanism that the executives adopted had not fully accommodated public aspirations to be stated by the DPRD as the general policies and directions (AKU) of the APBD. In the APBD discussion, available budgeting posts, in fact, had not considered priority scale of public needs as resulted from discussed mechanism referring of the previous-year APBD and they tended to be based on agreements between the executives and legislative and less fulfilled the performance-based budgeting principles. In the realization stage of APBD, controlling performed through field monitoring activities and work-metting (evaluation) actually had encountered technical and juridical obstacles. Meanwhile, controlling the Responsibility Report (LPJ) of regent as evaluation measure faced political aspects differences in maintaining the credibility of authority for the sake leadership existence. Also, it neglected technical aspects that should be directed to the APBD management ang exploitation to measure performance results of apparatus (executives) in order to realize good governance.The research recommends that to optimize controlling function of the DPRD in the APBD realization, warking standard on prioritized development to identify its synchronization with implemented budgeting posts on the APBD and monthly regular monitoring toward government pervormance to early detect available deviation are required.The empowerment of the DPRD members is performed through understanding better budgating posts in development sectors and routine budged that the executive propose. Improved controlling function of the DPRD (Local Legislative Assembly) on the Responsibility Report (LPJ) of Regent should be performent through governments pervormence assessment that ultimately leads to good governance indicated from minimum deviation of realized APBD in Merauke districk.